2006
DOI: 10.1177/089686080602600310
|View full text |Cite
|
Sign up to set email alerts
|

What is the Optimal Dwell Time for Maximizing Ultrafiltration with Icodextrin Exchange in Automated Peritoneal Dialysis Patients?

Abstract: Background Icodextrin is increasingly being used in automated peritoneal dialysis (APD) for the long dwell exchange to maintain adequate ultrafiltration (UF). However, the UF reported in the literature varies with different dwell times: from 200 to 500 mL with 12 – 15 hour dwells. In order to maximize UF, it is important to know the relationship between dwell time and UF when using icodextrin in APD patients. With this knowledge, decisions can be made with respect to dwell period, and adjustments to the dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…Although there are no previous studies that analyzed intraperitoneal dialysate volumes in patients receiving icodextrin for as long as 16 h using RISA volume marker, our results are in general agreement with some previous studies. Thus, as reported by Davies (2006), most randomized controlled clinical trials show that when using icodextrin solution, average net UF increases after 8 h of long day dwell in APD and up to 16 h of long night dwell in CAPD and this was confirmed in several recent studies (Jeloka et al, 2006; Lin et al, 2009; Takatori et al, 2011; Wang et al, 2015; Chang et al, 2016). However, results are not entirely consistent and great inter-individual variability of net UF has been reported.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although there are no previous studies that analyzed intraperitoneal dialysate volumes in patients receiving icodextrin for as long as 16 h using RISA volume marker, our results are in general agreement with some previous studies. Thus, as reported by Davies (2006), most randomized controlled clinical trials show that when using icodextrin solution, average net UF increases after 8 h of long day dwell in APD and up to 16 h of long night dwell in CAPD and this was confirmed in several recent studies (Jeloka et al, 2006; Lin et al, 2009; Takatori et al, 2011; Wang et al, 2015; Chang et al, 2016). However, results are not entirely consistent and great inter-individual variability of net UF has been reported.…”
Section: Discussionsupporting
confidence: 68%
“…However, results are not entirely consistent and great inter-individual variability of net UF has been reported. Jeloka et al (2006) reported that there was no increase in net UF in patients treated by APD when their dwell time with icodextrin solution was extended from 10 h to up to 14 h; however, re-analysis of the data showed that 16 (44%) of the patients had steadily increasing UF after 10 h (Venturoli et al, 2009). Furthermore, one study did not find any statistically significant differences in UF when comparing 49 patients on ICO with 51 patients on glucose solutions for 12 months follow-up (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] Another study by Jeloka et al showed that UF does not increase after a 10-hour dwell with icodextrin. 43 Based on this, Dousdampanis and colleagues hypothesized that two 8-hour exchanges with icodextrin could produce more UF than a single 15-16hour exchange. 44 In their study (n ϭ 9), they stated that none of the parameters tested were signifi cant and that caution should be exercised when using twicedaily icodextrin as RRF may decrease due to increased peritoneal UF, there may be increased infl ammatory responses as well as increased cost and there may be possible long-term effects of glucose polymer and maltose accumulation.…”
Section: New Osmotic Agentsmentioning
confidence: 99%
“…Early studies of icodextrin as a long dwell PD solution evaluated its metabolism, safety profile, and dialysis adequacy relative to glucose-based PD solutions (10)(11)(12)(13). In several studies, sodium removal with icodextrin was reported only for the study population as a whole (14)(15)(16)(17) and the dependence of UF on patient transport characteristics was discussed in a limited number of cases (18,19). In the present study, we used the 3-pore model to address these data gaps and illustrate the potential simplification and optimization of the dialysis prescription across patient transport groups when using icodextrin.…”
mentioning
confidence: 99%